Risk for severe outcomes of COVID-19 and PIMS-TS in children with SARS-CoV-2 infection in Germany - Sorg, Anna-Lisa; Hufnagel, Markus; Doenhardt, Maren; Diffloth, Natalie; Schroten, Horst; von Kries, Rüdiger; Berner, Reinhard; Armann, Jakob (European journal of pediatrics, 2022)
Although children and adolescents have a lower burden of SARS-CoV-2-associated disease compared to adults, assessing the risk for severe outcomes among SARS-CoV-2-infected children remains difficult due to a high rate of undetected cases. We combine data from three data sources — a national seroprevalence study (the SARS-CoV-2 KIDS study), the nationwide, state-based reporting system for PCR-confirmed SARS-CoV-2 infections in Germany, and a nationwide registry on children and adolescents hospitalized with either SARS-CoV-2 or pediatric inflammatory multisystem syndrome (PIMS-TS, also known as MIS-C) — in order to provide estimates on the risk of hospitalization for COVID-19-related treatment, intensive care admission, and death due to COVID-19 and PIMS-TS in children. The rate of hospitalization for COVID-19-related treatment among all SARS-CoV-2 seropositive children was 7.13 per 10,000, ICU admission 2.21 per 10,000, and case fatality was 0.09 per 10,000. In children without comorbidities, the corresponding rates for severe or fatal disease courses were substantially lower. The lowest risk for the need of COVID-19-specific treatment was observed in children aged 5-11 without comorbidities. In this group, the ICU admission rate was 0.37 per 10,000, and case fatality could not be calculated due to the absence of cases. The overall PIMS-TS rate was 2.47 per 10,000 SARS-CoV-2 infections, the majority being children without comorbidities.
Gesehen am 04.09.2023